The business of dental practice - Niken Widyanti Sriyono (Dental Journal (Majalah Kedokteran Gigi), 2006)
Globalization including General Agreement on Trade in Services (GATS) and Asia Fair Trade Agreement (AFTA) are a new free trade system. In globalization era, there will be an intense and free competition in looking for jobs throughout the world. This new system will affect the health services system in which health services tend to follow an industrial model. Meaning that dentistry or dental health services tend to be part of a business system, and this system has caused controversy among the community and the profession itself. The results of the discussion revealed that professional and business of dentistry is compatible and complementary. The tendency of increasing number of legal form of practice (group and a professional corporation) and the worldwide advertisement of these practices supported the premise that delivering dental practice tends to follow the industrial model. Dentists should not only more focus on achieving financial success in running the business of practice but profession should have the most concern for the people who seek their services. Delivering quality of dental care depends on the high skill of the dentist and on the satisfactory income for the survival of the practice in the long run, and this make the practice will be viewed by the public and profession as being appropriate and of high quality. Facing the globalization, besides possessing high clinical skill, dentists must have a firm understanding of management concepts and apply them in their practice. In conclusion: The profession and the business of dentistry are compatible and complementary. The delivery of the dental services tends to follow the industrial model, which is a current reality. Dentist should concern more on the delivering high quality of dental services, not only focus on the business of the practice, although the satisfactory income is important for the survival growth of the practice in the long run. It is suggested for dentists to follow as much business training or dental practice management training as the dentist can. It is also suggested to give the undergraduate students the basic concepts of dental practice management by putting this in the curriculum.